FIRE CONTROL SYSTEM STOREY BUILDINGS - Okti Suryandari; Jalinas Jalinas, SKom, MM (Jurnal Sistem Komputer, 2002)
Tool works in accordance with the desired. Temperature sensors will provide logic low if exposed to heat above 50 degrees Celsius and provides logic high if the normal temperature.Â  Relay logic would work if it gets high (for sensor and electrical fires) are assumed to be connected to the pump relay, so the pump working and the temperature drops, the pump will stop automatically.Â Â